Leadership quality and competency towards investor valuation and firm performance - Mat Dangi, Mohamad Ridhuan; Abdul Latif, Nurul Ezhawati; Baharum, Zafiruddin; Mohd. Noor, Rohana (Penerbit Akademia Baru, 2017)
Leadership is one of the most important considerations when look up on a potential investment. As such, quality leadership also reflects the quality management as well as ensuring the success of the investment. Some investors view the quality of leadership, culture and the quality of relationships with core stakeholders as critical factors and become the important criteria when choosing companies to invest. Investors will seek what is really worth when making an investment which normally represents the value of the firm. It was learned that investors define the market value of the firm not just based on financial performance. They also gain more interest on intangibles like strategy, brand, innovation, research and development, collaboration and so on. In recent years, it was discovered that researchers also found a wise long term investors recognize that leadership also affects firm performance. This paper provides multiple reviews about the importance of the leadership behaviour as another discipline in firm valuation. It is expected that this paper will give more insight to investors where they are able to reduce the overall investment risk, improve the chances of investment success and build investors’ and organizational confident.